The rise of securitization impacts on banks credit risk management: Empirical evidence from the US commercial banks - duan, xiaotong (2018)
The main purpose of this study is to investigate the impact of securitization on bank credit risk-taking behavior. Previous research has not reached a consensus whether securitization can have a negative or a positive effect on the risk of bank failure. In our paper, we used data from major US commercial banks during the financial crisis between 2002 and 2016, and selected banks that had securitized activities during the financial crisis. Using the securitization human OLS regression and panel method, we observed a positive relationship between securitization and banks’ credit risk-bearing behavior. In addition, we also find that the positive correlation between credit risk securitization and bank credit risk is mainly driven by non-mortgage securitization assets, and mortgage securitization assets seem to have no significant impact on credit risk. And it seems that commercial banks with higher profits tend to take on more risks. This result shows that the current financial storm is closely related to credit risk securitization. Once the current problems in the credit market are solved, securitization activities may start again, which may lead to another global financial turmoil.